A new species of Ommatius Wiedemann (Diptera: Asilidae) from Brazil - Vieira, Rodrigo; Castro, Ivan; Bravo, Freddy (Zootaxa, 2005)
Ommatius riali sp. nov. is described from the state of Bahia, Brazil. This species belongs to the Neotropical costatus group, thus increasing to seventeen the number of known species. The structures of terminalia are illustrated and described, and a new key to the Neotropical costatus species group is proposed.